PROGNOSTIC VALUE OF THE NEUTROPHIL-TO-LYMPHOCYTE COUNT IN PATIENTS WITH LIVER CIRRHOSIS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Liver cirrhosis is a gradual and irreversible chronic hepatic condition marked by fibrosis and regenerating nodules. Identifying dependable, cost-effective, and accessible prognostic indicators is essential for informing therapeutic decisions and enhancing patient outcomes. Recently, the neutrophil-to-lymphocyte ratio (NLR), a measure of systemic inflammation, has surfaced as a potential prognostic marker in numerous diseases, including cancers, cardiovascular disorders, and chronic liver diseases. Aims: To evaluate the NLR in patients with liver cirrhosis and to determine the correlation between NLR and the severity of liver cirrhosis using Child-Pugh and MELD scoring systems. Methods: A cross-sectional observational study was carried out at a tertiary care hospital from January to June 2025. Seventy patients identified with liver cirrhosis validated through clinical, biochemical, and radiological assessments—were included. Individuals with simultaneous infections, cancers, or autoimmune diseases were excluded. Complete blood counts were acquired upon admission, and the neutrophil-to-lymphocyte ratio (NLR) was determined by dividing the absolute neutrophil count by the absolute lymphocyte count. Patients were categorized based on Child-Pugh and MELD scores to evaluate illness severity. The correlation between NLR and clinical outcomes, such as hepatic decompensation, length of hospitalization, and mortality, was examined utilizing suitable statistical techniques. Results: The mean NLR value was considerably higher in individuals with decompensated cirrhosis relative to those with compensated illness (6.2 vs. 2.8, p < 0.01). Patients classified as Child-Pugh class C exhibited significantly higher NLR levels than those in classes A and B. A positive association was identified between NLR and MELD scores (r = 0.49, p < 0.01), signifying deteriorating liver function with heightened inflammatory response. Moreover, those exhibiting elevated NLR values (>5.0) experienced prolonged hospitalizations and an increased in-hospital mortality rate. Conclusion: The NLR is a simple, cost-effective and easily available biomarker that has a substantial correlation with the severity of liver cirrhosis and clinical outcomes. Increased NLR correlates with heightened illness severity scores, augmented risk of comorbidities, and elevated mortality rates.